BIOENSAIOS DE RELEVÂNCIA MEDICINAL APLICADOS EM UM NOVO COMPOSTO DE COORDENAÇÃO - Favero, Vanessa; Macedo, Michele; Biscoli, Leandro; Sotto, Jaqueline; Dos Anjos, Ademir; Faganello, Natali (ANAIS DO ENIC, 2018)
-